Intestinal Commitment and Maturation of Human Pluripotent Stem Cells Is Independent of Exogenous FGF4 and R-spondin1 - Tamminen, Kaisa; Balboa, Diego; Toivonen, Sanna; Pakarinen, Mikko P.; Wiener, Zoltan; Alitalo, Kari; Otonkoski, Timo (PLOS ONE, 2015)
Wnt/beta-catenin signaling plays a central role in guiding the differentiation of the posterior parts of the primitive gut tube into intestinal structures in vivo and some studies suggest that FGF4 is another crucial factor for intestinal development. The aim of this study was to define the effects of Wnt and FGF4 on intestinal commitment in vitro by establishing conditions for differentiation of human pluripotent stem cells (hPSC) into posterior endoderm (hindgut) and further to self-renewing intestinal-like organoids. The most prominent induction of the well-established intestinal marker gene CDX2 was achieved when hPSC-derived definitive endoderm cells were treated with Wnt agonist molecule CHIR99021 during differentiation to hindgut. FGF4 was found to be dispensable during intestinal commitment, but it had an early role in repressing development towards the hepatic lineage. When hindgut stage cells were further cultured in 3D, they formed self-renewing organoid structures containing all major intestinal cell types even without exogenous R-spondin1 (RSPO1), a crucial factor for the culture of epithelial organoids derived from adult intestine. This may be explained by the presence of a mesenchymal compartment in the hPSC-derived organoids. Addition of WNT3A increased the expression of the Paneth cell marker Lysozyme in hPSC-derived organoid cultures, whereas FGF4 inhibited both the formation and maturation of intestinal-like organoids. Similar hindgut and organoid cultures were established from human induced pluripotent stem cells, implying that this approach can be used to create patient-specific intestinal tissue models for disease modeling in vitro.